The Aryl Hydrocarbon Receptor in the Pathogenesis of Environmentally-Induced Squamous Cell Carcinomas of the Skin - Vogeley, Christian; Rolfes, Katharina M.; Krutmann, Jean; Haarmann-Stemmann, Thomas (Frontiers in Oncology, 2022)
Cutaneous squamous cell carcinoma (SCC) is one of the most frequent malignancies in humans and academia as well as public authorities expect a further increase of its incidence in the next years. The major risk factor for the development of SCC of the general population is the repeated and unprotected exposure to ultraviolet (UV) radiation. Another important risk factor, in particular with regards to occupational settings, is the chronic exposure to polycyclic aromatic hydrocarbons (PAH) which are formed during incomplete combustion of organic material and thus can be found in coal tar, creosote, bitumen and related working materials. Importantly, both exposomal factors unleash their carcinogenic potential, at least to some extent, by activating the aryl hydrocarbon receptor (AHR). The AHR is a ligand-dependent transcription factor and key regulator in xenobiotic metabolism and immunity. The AHR is expressed in all cutaneous cell-types investigated so far and maintains skin integrity. We and others have reported that in response to a chronic exposure to environmental stressors, in particular UV radiation and PAHs, an activation of AHR and downstream signaling pathways critically contributes to the development of SCC. Here, we summarize the current knowledge about AHR’s role in skin carcinogenesis and focus on its impact on defense mechanisms, such as DNA repair, apoptosis and anti-tumor immune responses. In addition, we discuss the possible consequences of a simultaneous exposure to different AHR-stimulating environmental factors for the development of cutaneous SCC.